The Effect Of Parenting Style On Adolescent’s Perception Towards Road Safety (International Journal of Built Environment and Sustainability, 2019)
The purview of this paper is to analyze the relationships between parenting styles and adolescent risk behaviors on the road due to the critical parental role in preventing crashes among teens. The objectives  of this research are to list different parenting styles that may influence adolescent behavior, to assess the relationship between parenting styles and adolescent’s perception towards road safety, to determine which parenting style that promotes a desirable street protection habits among adolescent, and to propose a framework that integrated parenting style to road safety program. Descriptive and statistical analyses are used in this paper to interpret the data taken from 298 questionnaire-respondents which the parallel between the desired parenting style and the adolescent’s good perception of road safety is cast using the Pearson Correlation Coefficient. A quantitative approach is employed in processing the data taken from those selected respondents then the qualitative data is composed and operated to complete the quantitative data by giving more comprehensive knowledge over the argumentation and more description of the quantitative result. More so, the study supports the substantial influence of parenting style on adolescent development such as the adolescents who are raised in authoritative households consistently demonstrate higher protective and fewer risk behaviors than adolescents from non-authoritative families.
Keywords: Parenting styles; Adolescent; Road Safety